PRACA ZAWODOWA KOBIET JAKO CZYNNIK ZMIANY DEMOGRAFICZNEJ - Ochocki, Andrzej (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article discusses the relation between parenthood and work on the basis of five coun¬tries: Finland, Germany, Poland, the Czech Republic and Italy. The theoretical basis of the analysis is Gary S. Becker’s thesis that there is the interaction between the number of children born in a given family and elements referring to the quality of those children that is their general health, education, talents which they develop and systems of values which they acquire. The conclusion seems to be that whenever total family income rises, parents are more willing to invest money in human capital of children they already have rather than increase the number of children. The analysis, also, proves that professional activity of mothers looking after their small children is conditioned by both the level of well-being of the respective society and solutions shaping the family policy. The hypothesis could also be formulated that indirect public transfers in the form of institutional child care stimulate professional activity of mothers as well as fertility.